2005
DOI: 10.1021/ja055129t
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Mediated Electron Configuration Change in High-Spin Iron(II) Porphyrinates

Abstract: Heme proteins carry out a phenomenal range of biological processes with a common prosthetic group and a relatively small variety of axial ligands. In this paper, we report the effects on the molecular and electronic structure when the imidazole ligand is deprotonated in five-coordinate iron(II) [Fe(Por)(2-MeHIm)] derivatives. 1 Although imidazole-and imidazolate-ligated iron (II) porphyrinates both exhibit an S = 2 (quintet) state, the coordination group geometries are distinctly different with axial and equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 8 publications
7
49
0
Order By: Relevance
“…These differences are schematically depicted in Figure 2 for the iron(II) derivatives with imidazole and imidazol ate as the axial ligand. The values shown for imidazolate are the averages for the structures reported earlier12 and those for the imidazole averages are drawn from previously defined structures 10, 11, 1315 Although both types of species are high-spin ( S = 2), the coordination geometry differences are striking.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are schematically depicted in Figure 2 for the iron(II) derivatives with imidazole and imidazol ate as the axial ligand. The values shown for imidazolate are the averages for the structures reported earlier12 and those for the imidazole averages are drawn from previously defined structures 10, 11, 1315 Although both types of species are high-spin ( S = 2), the coordination geometry differences are striking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on imidazole- and imidazolate-ligated five-coordinate iron(II) porphyrinates have shown that these represent two distinct groups with different electronic configurations 10,11,13. Mössbauer spectra of the imidazolate-ligated and other anionic-ligated species show a large positive value of the quadrupole splitting with a small asymmetry parameter (η); they have the normal doubly occupied d xy ground state, (d xy ) 2 (d xz ) 1 (d yz ) 1 −(d z 2 ) 1 (d x 2 − y 2 ) 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This series follows the order of the importance of iron to ligand π -backbonding, with the smallest π -bonding in the imidazole complex. 75 The axial Fe–N bond distances in the three systems are 1.722, 90 2.058, 91 and 2.147 Å, 39 respectively.…”
Section: Discussionmentioning
confidence: 98%